2011
DOI: 10.1094/pdis-06-10-0450
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Resistance to Phakopsora pachyrhizi in Soybean

Abstract: Resistance in soybean to Phakopsora pachyrhizi, the cause of soybean rust, is characterized by either reddish-brown (RB) lesions or an immune response. The RB type of resistance can be incomplete, as evidenced by the presence of sporulating uredinia within lesions. Susceptibility, on the other hand, is exemplified by tan-colored (TAN) lesions, and can be expressed in gradations of susceptibility or partial resistance that are less well defined. This study evaluated traits associated with incomplete or partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
1
40
0
2
Order By: Relevance
“…Because of the wide range of variation in infection types (i.e., RB or TAN lesions) with regard to color and intensity of sporulation from pustules, infection type was not used as a major rating determinant in this study. Furthermore, Miles et al (2011) concluded that lesion type was not associated with disease severity in a group of 34 accessions inoculated with four P. pachyrizi isolates in the greenhouse. Bromfield (1984) himself later acknowledged that three infection type descriptions (including the symptomless immune response) were inadequate for describing the full range of lesion appearances observed, and other researchers have reached a similar conclusion (Bonde et al, 2006;Kato and Yorinori, 2008;Morel et al, 2008).…”
Section: Evaluation and Rating Methodsmentioning
confidence: 91%
“…Because of the wide range of variation in infection types (i.e., RB or TAN lesions) with regard to color and intensity of sporulation from pustules, infection type was not used as a major rating determinant in this study. Furthermore, Miles et al (2011) concluded that lesion type was not associated with disease severity in a group of 34 accessions inoculated with four P. pachyrizi isolates in the greenhouse. Bromfield (1984) himself later acknowledged that three infection type descriptions (including the symptomless immune response) were inadequate for describing the full range of lesion appearances observed, and other researchers have reached a similar conclusion (Bonde et al, 2006;Kato and Yorinori, 2008;Morel et al, 2008).…”
Section: Evaluation and Rating Methodsmentioning
confidence: 91%
“…The responses described most frequently include the (i) immune reaction (IM) without visible lesions, indicating an incompatible host-parasite interaction; (ii) RB lesions without sporulation (complete resistance); (iii) RB lesions with varying levels of sporulation (incomplete resistance); (iv) tan-colored lesions (TAN) with limited sporulation (partial resistance); and (v) TAN lesions with abundant urediniospore production (susceptible reaction) (3,25,30). Based on genetic analyses of phenotypes within segregating populations developed from crossing parents having IM or RB resistant phenotypes with TAN susceptible parents, six soybean rust resistance loci (Rpp1-Rpp5, some multi-allelic) have been identified and mapped in the soybean genome, and the interaction of these loci with P. pachyrhizi pathotypes has been summarized (9).…”
mentioning
confidence: 99%
“…According to studies from Miles et al [49], the rust severity was not related to the type of lesions. Among the varieties with RB lesions, PI 561356 and PI 594538A showed lower levels of severity than PI 230970, PI 423972 and PI 459025B, who were the varieties with higher rates of severity.…”
Section: Resistancementioning
confidence: 96%
“…According Parlevliet [47] and Ribeiro Do Vale [48], incomplete resistance allows some growth or reproduction of the pathogen in the host tissues. Finally, the tan colored lesions (TAN), indicative of susceptibility [49]. Either IM or RB reaction are initiated with the early perception of the pathogen avirulence proteins by plant R proteins, according the classical gene-for-gene resistance theory [50].…”
Section: Resistancementioning
confidence: 99%
See 1 more Smart Citation